Análise dos sistemas de logística reversa em municípios da bacia hidrográfica Tietê-Jacaré (UGRHI-13) - Corrêa, Fernanda Defourny (Universidade Federal de São Carlos, 2019)
The National Solid Waste Policy, established by Law No. 12,305 of August 2, 2010, regulated by Decree No. 7,404 of 2010, obliges manufacturers, importers, distributors and retailer of pesticides, their residues and packaging; batteries; tires; lubricating oils, their residues and packaging; fluorescent lamps, sodium and mercury vapor and mixed light; electronic products and their components; and packaging in general to implement Reverse Logistics (RL) systems, returning the products after the use by consumers to the production cycle or other environmentally adequate final destination. The importance of establishing an adequate solid waste management system is not only related to minimizing impacts on the environment, but also on public health. Thus, the objective of this work is to analyze the RL implementation in the municipalities of the HRMU (Hydric Resources Management Unit) -13, of the post-consumption products of the productive sectors already mentioned. The methods adopted include the documentary analysis and the application of a questionnaire in municipalities for the collection of institutional data and management guidelines, and for the case study in the municipality of São Carlos, a detail of the actions through dialogue and interviews with the actors involved in RL systems - municipal public power, resellers of products related to the research, associations representing the productive sectors, managing entities of RL, and other organizations that carry out RL actions. It was identified, among the results, formal and informal RL initiatives in the municipalities of HRMU-13; and that municipalities have no knowledge of all the RL systems that are being implemented; which among these initiatives identified the RL tire system as the one with the highest representativeness among municipalities; and that there is a lack of cooperation between the public spheres and between the private sector and municipalities
Analysis of reverse logistic systems in the municipalities of the Tietê-Jacaré hydrographic basin (HRMU -13).
Keywords: Logística reversa; Política Nacional de Resíduos Sólidos; Municípios da UGRHI-13; Reverse logistic; National Waste Policy; Municipalities of HRMU-13; OUTROS